Molybdenum incorporated mesoporous silica catalyst for production of biofuels and value-added chemicals via catalytic fast pyrolysis1. Issue 5 (12th May 2015) - Budhi, Sridhar; Mukarakate, Calvin; Iisa, Kristiina; Pylypenko, Svitlana; Ciesielski, Peter N.; Yung, Matthew M.; Donohoe, Bryon S.; Katahira, Rui; Nimlos, Mark R.; Trewyn, Brian G.
<x xml:space="preserve">Abstract</x> Production of furans and phenols from biomass through catalytic fast pyrolysis of pine using Mo-supported KIT-5 mesoporous silica was explored.